PENGARUH LITERASI EKONOMI, LITERASI DIGITAL DAN ADVERSITY QUOTIENT TERHADAP DIGITAL ENTREPRENEURSHIP INTENTION MAHASISWA - Cici Sri Wahyuni; Edi Fitriana Afriza; Astri Srigustini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of economic literacy, digital literacy, and adversity quotient on students' digital entrepreneurship intention partially and simultaneously. This research employs a survey method with the population consisting of students from the Sharia Economics Study Program at Universitas Siliwangi, class of 2021–2023. The sample was selected using proportionate stratified random sampling technique, totaling 214 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that: 1) Economic literacy has a positive and significant effect on Digital Entrepreneurship Intention with a significance value of 0.000 <0.05. 2) Digital Literacy has a positive and significant effect on Digital Entrepreneurship Intention with a significance value of 0.000 <0.05. 3) Adversity Quotient has a positive and significant effect on Digital Entrepreneurship Intention with a significance value of 0.000 <0.05. 4) Economic Literacy, Digital Literacy and Adversity Quotient simultaneously affect Digital Entrepreneurship Intention as evidenced by Fcount 202.695 > F table 2.65 with a significance value obtained of 0.000 < 0.05.